The Relationship Between The Nutritional Status of Toddlers and Family Economic Status During The Pandemic in The Village of Ciladeun Lebak- Banten - Putri Nazua Mas'ud; Rika Ferlianti (Junior Medical Journal, 2023)
The results of the Ministry of Health's Indonesian Nutrition Status Study (SSGI) survey recorded that 24.5% of babies under five years of age (toddlers) in Banten Province were stunted in 2021. Pandeglang Regency was recorded as the region with the highest prevalence of stunted toddlers in Banten, reaching 37.8% last year. Economic status in the family is essential in supporting children's growth and development. In addition, the nutritional status of toddlers is also very dependent on the parenting of parents or their environment on the quality of food, nutrients and physical health. This study aims to provide an overview of the nutritional status of toddlers from family economic status during the pandemic in Ciladeun village, Lebak-Banten. This research method is descriptive-analytic with a quantitative approach and research design using cross-sectional. Data collection techniques in this study used interviews and questionnaires. Data analysis used the SPSS Statistic version 24 and univariate and bivariate analysis. The results showed that the nutritional status of toddlers 2-5 years had a "normal" nutritional status of 73.9%. Family economic status with nutritional status in children under five years old has no significant relationship. The parenting of feeding by mothers with children under five is said to be "appropriate" by 53.6%. The social status of the family that the wife's work status as a housewife was 81.2%. So this study concludes that nutritional status with economic status before and after the pandemic in toddlers there is no significant relationship between income before and after the pandemic with the nutritional status of toddlers in Ciladeun Village, Lebak-Banten.   Kesehatan mencatat 24,5% bayi usia di bawah 5 tahun (Balita) di Provinsi Banten mengalami stunting pada 2021.Kabupaten Pandeglang tercatat sebagai wilayah dengan prevalensi Balita stunting tertinggi di Banten, yakni mencapai 37,8% pada tahun lalu. Status ekonomi pada keluarga sangat penting dalam mendukung tumbuh kembang anak. Selain itu, status gizi balita juga sangat bergantung pada pola asuh orang tua atau lingkungannya terhadap kualitas makanan, zat gizi serta kesehatan fisik.Penelitian ini bertujuan untuk memberikan gambaran status gizi balita dari status ekonomi keluarga selama pandemi di desa Ciladeun Lebak-Banten. Metode penelitian ini adalah analitik deskriptif dengan pendekatan kuantitatif dan desain penelitan menggunakan cross sectional. Teknik pengumpulan data dalam penelitian ini menggunakan cara wawancara dan kuisioner. Analisis data menggunakan aplikasi SPSS Statistic versi 24 dan menggunakan analisis univariat serta analisis bivariat. Hasil penelitian menunjukkan bahwa Status gizi pada balita 2-5 tahun memiliki status gizi yang “normal” sebesar 73,9%. Status ekonomi keluarga dengan status gizi  pada anak balita tidak terdapat hubungan signifikan. Pola asuh pemberian makan oleh ibu pada anak balita dikatakan “tepat” sebesar 53,6%. Status sosial keluarga bahwa pekerjaan istri berstatus sebagai ibu rumah tangga sebesar 81.2%. Sehingga penelitian ini menyimpulkan bahwa status gizi  dengan status ekonomi sebelum dan sesudah pandemi pada balita tidak terdapat hubungan yang signifikan antara pendapatan sebelum dan sesudah pandemi dengan status gizi balita Di Desa Ciladeun Lebak-Banten.